Insertion of a Love-Based Curriculum in Multicultural Islamic Religious Education - Danil, Harling; Syafaruddin, Baso; Sarda, Muh (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Islamic Religious Education in the contemporary era faces challenges in developing the character of students capable of living harmoniously in a multicultural society. This study examines the insertion of a love-based curriculum as an innovative solution in multicultural Islamic religious education. A love-based curriculum is an educational approach that integrates the values of compassion, tolerance, and empathy as the foundation of Islamic religious learning in the context of diversity. Through literature analysis and conceptual studies, this study explores the theoretical foundations, practical implementation, and potential impacts of a love-based curriculum. The results of the study indicate that a love-based curriculum can be a bridge connecting a profound understanding of religion with a tolerant attitude towards diversity. Its implementation requires transformations in learning approaches, teacher competencies, and a holistic evaluation system. This curriculum has the potential to produce a generation of Muslims with balanced spiritual, emotional, and social intelligence, capable of becoming agents of peace in a multicultural society. Implementation challenges include community resistance, limited resources, and the complexity of material development. However, great opportunities are open with the support of religious moderation policies and Indonesia's diversity as a natural laboratory. In conclusion, the insertion of a love-based curriculum in multicultural Islamic education is an urgent need to build a more peaceful and harmonious civilisation.